2008
DOI: 10.1371/journal.pone.0001768
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mapping of Movement-Associated Areas in the Avian Brain: A Motor Theory for Vocal Learning Origin

Abstract: Vocal learning is a critical behavioral substrate for spoken human language. It is a rare trait found in three distantly related groups of birds-songbirds, hummingbirds, and parrots. These avian groups have remarkably similar systems of cerebral vocal nuclei for the control of learned vocalizations that are not found in their more closely related vocal non-learning relatives. These findings led to the hypothesis that brain pathways for vocal learning in different groups evolved independently from a common ance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
447
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 279 publications
(490 citation statements)
references
References 121 publications
(259 reference statements)
38
447
5
Order By: Relevance
“…Our results may shed light on the evolution of vocal-learning circuits, which have been proposed to have emerged either from a descending auditory pathway that then added a motor function 39,40 ; or, conversely, that motor pathways became overlaid by auditory control 41 . It has been suggested that in pigeons (Columbiformes), part of the Nd and Ai are thought to be homologous to the auditory 'shelf' and the auditory 'cup' adjacent to the oscine HVC and RA respectively.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our results may shed light on the evolution of vocal-learning circuits, which have been proposed to have emerged either from a descending auditory pathway that then added a motor function 39,40 ; or, conversely, that motor pathways became overlaid by auditory control 41 . It has been suggested that in pigeons (Columbiformes), part of the Nd and Ai are thought to be homologous to the auditory 'shelf' and the auditory 'cup' adjacent to the oscine HVC and RA respectively.…”
Section: Discussionmentioning
confidence: 84%
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms3082 ARTICLE song and other motor activity that occurs at the same time as birds sing 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical terminology used in this paper follows the new avian brain nomenclature (Reiner et al 2004;Jarvis et al 2005) with modifications ( Feenders et al 2008; see abbreviations list). For visually activated areas adjacent to and near the entopallium (E) of the tectofugal pathway that have been called lateral nidopallium and lateral ventral mesopallium, we called them nidopallium adjacent to the entopallium (Ne) and ventral mesopallium near the entopallium (MVe).…”
Section: (D) Anatomymentioning
confidence: 99%
“…Standard in-situ hybridization methods take longer to seal the slides with parafilm, nail polish, and other means, where slides take up a lot of space; (3) It is highly sensitive for low abundance transcripts due to Dextran sulfate and Denhardt's solution in the hybridization buffer 2,13 ; (4) The imaging approach in darkfield yields high contrast images due to taking pictures under darkfield illumination on a dissecting microscope 4,5 . Additionally, It allows sensitive detection of small changes in gene expression, such as in activity-dependent gene expression to identify specific brain regions activated during perception and production of specific behaviors 19 . The limitations relative to non-radioactive protocols are that the latter are clearer in the cellular resolution and location of the mRNA within the cell, and working with emulsion is very sensitive to manipulation and light.…”
Section: Discussionmentioning
confidence: 99%